دور عوامل رأس المال البشري في الحصول على فرص عمل حر عبر شبكة الانترنت، دراسة تطبيقية على شركات العمل الحر في فلسطين: THE ROLE OF HUMAN CAPITAL FACTORS IN OBTAINING FREELANCE OPPORTUNITIES ONLINE: AN APPLIED STUDY ON FREELANCING COMPANIES IN PALESTINE - Alshaikhkhalil , Bahi; Johari , Fuadah (I-iECONS e-proceedings, 2023)
: تهدف الدراسة إلى معرفة العوامل المكونة لرأس المال البشري والتي تؤثر في التوظيف الحر بواسطة الانترنت والتي تكونت من (التدريب، الخبرة، التعليم، المهارة) بالتطبيق على الشركة العاملة في مجال العمل الحر والحاضنات في قطاع غزة. تبنت الدراسة الراهنة المنهج الوصفي التحليلي بالاعتماد على اداتي الاستبانة والمقابلة المعمقة لجمع البيانات من مصادرها الأولية، حيث تمثل مجتمع الدراسة بالعامين بشركات العمل عن بعد والحاضنات التكنولوجية العاملة في قطاع غزة والبالغ عددهم (375) موظفاً تم ارسال الاستبانة إليهم وتعبئتها لأغراض تحقيق اهداف الدراسة، حيث اعتمد الباحث على أسلوب المسح الشامل لاستقاء البيانات من مصادرها الأولية. توصلت الدراسة الى جملة من النتائج تمثل أهمها في وجود علاقة ارتباط إيجابية بين عوامل راس المال البشري والحصول على فرص عمل حر عبر الانترنت، كما اظهرت النتائج وجود أثر إيجابي معنوي لعوامل راس المال البشري في خلق فرص عمل حر عبر الانترنت. اوصت الدراسة بضرورة قيام الجهات الحكومية بتبني نموذج العمل الحر في المناطق الفلسطينية كوسيلة مثالية للحد من تفاقم مشكلة البطالة. This study aims to identify the components of human capital that influence online freelance employment, which include training, experience, education, and skills. The study applies these factors to freelancing companies and technology incubators operating in Gaza. The research adopts a descriptive-analytical approach, utilizing survey and in-depth interviews as data collection methods. The study population includes employees of remote work companies and technology incubators in Gaza, totaling 375 individuals who received and completed the survey to achieve the study's objectives. The researcher relied on a comprehensive survey method to gather data from primary sources. The study yielded several results, with the most significant being the presence of a positive correlation between human capital factors and obtaining freelance opportunities online. The results also demonstrated a statistically significant positive impact of human capital factors on creating freelance opportunities online. The study recommends that governmental authorities in Palestinian territories adopt the freelance work model as an ideal solution to mitigate the unemployment problem.